2009
DOI: 10.2220/biomedres.30.271
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration fluoride stimulates cell motility of epithelial cells in vitro

Abstract: Oral mucosal tissue can serve as a long-term fluoride reservoir following topical application and retain a small amount of fluoride in oral environment for prevention of dental caries. The aim of this study was to determine the effect of low level sodium fluoride (NaF) on the proliferation and migration of epithelial cells in vitro. Human primary gingival epithelial cells and human epidermal HaCaT keratinocytes were used. Cultured epithelial cells, treated with various concentrations of NaF ranging from 5 μM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…We previously reported that low level NaF is able to induce cell motility, migration, invasion and matrix production in epithelial cells 23) . In this study, we identify the proteins involved in fluoride signaling and determine the role of these molecules in epithelial mesenchymal interactions in oral mucosa.…”
Section: Discussionmentioning
confidence: 95%
“…We previously reported that low level NaF is able to induce cell motility, migration, invasion and matrix production in epithelial cells 23) . In this study, we identify the proteins involved in fluoride signaling and determine the role of these molecules in epithelial mesenchymal interactions in oral mucosa.…”
Section: Discussionmentioning
confidence: 95%
“…The fluoride concentrations in our experiments were chosen according to a previous study that resulted in measurable effects on cultured cells. 19 Fluoride can inhibit the function of isolated osteoclasts at 0.5 to 1.0 mmol·L −1 in vitro . 20 Fluoridated drinking water markedly inhibited the bone resorption induced by hydrocortisone 21 and showed a lower histologic incidence of alveolar bone resorption after the injection of parathormone.…”
Section: Discussionmentioning
confidence: 97%
“…Each well was washed twice with PBS to remove debris and to smooth the edge of the scratch and then replaced with the serum‐free Huaier aqueous extract (4 mg/mL). After that, the migration of cells in the “scratch” was photographed at the matching reference points with phase‐contrast microscope for the first image, and the following images were taken at intervals of 12 h. ( 20,21 ) The images were analyzed quantitatively by ImageJ; the distances between the two edges of the scratch were measured at the reference points and analyzed statistically.…”
mentioning
confidence: 99%